The Effect of Health Promotion by Pender’s Theory for Behavior Change for High Blood Pressure control to Prevent Hypertension-related Complications among Elderly at Public Health Center Det udom District Ubon Ratchathani Province - มังคละพลัง รัญณชา; ลอยหา กุลชญา; วงษ์ประเสริฐ จำลอง (UBRU Journal for Public Health Research, 2017)
The research was a quasi-experimental study. It aimed to compare the differences of the mean scores of the health promotion program according to Pender’s theory in behavioral changes to control high blood pressures to prevent complications following the experiment between the experimental group and the control group. The subjects totaled 68 divided into two groups of 34 each. The experimental group underwent a health promotion program based on Pender’s concept on behavioral changes to control high blood pressure to prevent complications. The methods used were a visual slide display, a good model presentation, a training demonstration, a self-caring handbook, and focus group. Data were collected by a questionnaire. Descriptive statistics were used for general data and inferential statistics were used for comparative data. The research results revealed that following the experiment, the experimental group had a higher value of scores than before the experiment and higher than the comparative group in the aspects of perception of high blood pressure disease, of benefits and obstacles of health promotion to control blood pressure to prevent complications and behaviors to control high blood pressure and to prevent complications at a statistical significance of 0.05